Access to specialist hospital care and injury survivability: identifying opportunities through an observational study of prehospital trauma fatalities. Issue 10 (October 2021) - Davie, Gabrielle; Lilley, Rebbecca; de Graaf, Brandon; Ameratunga, Shanthi; Dicker, Bridget; Civil, Ian; Reid, Papaarangi; Branas, Charles; Kool, Bridget
Highlights: In New Zealand, 15% of prehospital trauma deaths are estimated to have potentially survivable injuries occurring in locations without timely hospital access More than half of the potentially survivable prehospital trauma fatalities without timely access died as a result of a motor vehicle traffic crash Geographical clusters of incident injury locations for survivable prehospital trauma deaths without timely hospital access can be identified Trauma service delivery should consider the geographic distribution of injury locations for prehospital deaths Abstract: Background: Of the five million injury deaths that occur globally each year, an estimated 70% occur before the injured person reaches hospital. Although reducing the time from injury to definitive care has been shown to achieve better outcomes for patients, the relationship between injury incident location and access to specialist care has been largely unexplored. Objective: To determine the number and distribution of prehospital (on-scene/en route) trauma deaths without timely access to a hospital with surgical and intensive care capabilities, overall and by estimated injury survivability. Methods: New Zealand's Mortality Collection and Hospital Discharge dataset were used to select prehospital injury deaths in 2009-2012. These records were linked to files held by Australasia's National Coronial Information Service (NCIS) to estimate, for the trauma subset, injury survivability. Using geographical locations of injury for the prehospital trauma fatalities, time from Emergency Medical System call-out to arrival at the closest specialist hospital was estimated. Results: Of 1, 752 prehospital trauma fatalities, 14.7% (95%CI 13.0, 16.4) had potentially survivable injuries that occurred in locations without timely access (prehospital phase >60 minutes). More than half (132 of 257) of the potentially survivable prehospital trauma fatalities without timely access died as a result of a motor vehicle traffic crash. Only 10% (95%CI 5.7, 16.0) of prehospital trauma fatalities from falls were estimated to be potentially survivable and without timely access compared to 24.6% (95%CI 18.5, 31.5) of prehospital firearm fatalities. Through using geospatial techniques, "hot spot" locations of potentially survivable injuries without timely access to specialist major trauma hospitals were apparent. Conclusion: Approximately 15% of prehospital trauma fatalities in New Zealand that are potentially survivable occur in locations without timely access to advanced level hospital care. Continued emphasis is required on both improving timely access to advanced trauma care, and on primary prevention of serious injuries. Decisions regarding trauma service delivery, a modifiable system-level factor, should consider the geographic distribution of locations of these injury events alongside the resident population distribution.